Rex Romae Recens Natus. Classical Motifs in the Occasional Poetry Celebrating the Birth of Napoleon’s Son - Fulińska, Agnieszka (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The birth in 1811 of the long-awaited heir to the French Empire resulted in literary creativity of both accomplished writers of the period and amateurs who took part in several poetic competitions or self-published their works. Due to the predominant classical model of education and symbolic language of the period, these works abounded in ancient allusions, motifs and themes, covering a broad range of mythological and historical figures and places. This paper seeks to assess the spectrum of the authors’ knowledge and versatility with classical topics by presenting both an approximation of the frequency of mythological personages, and a survey of the roles they played in the imaginarium of the authors, who rarely were professional teachers of ancient literature or history. The compiled material gives insight not only into the ways in which the birth of the imperial prince was represented in literature, but also into the knowledge of classics among ordinary educated people of the period.